Analysis of the Influence of Marketing Technology Concepts, Service Quality, and Low-Cost Carrier on Customers and Customer Loyalty on Lion Air Airlines in Indonesia - Vivid Violin; Mahfudnurnajamuddin; Sabri Hasan; Muhlis Sufri (Junal Ilmu Manajemen, 2022)
This research uses a quantitative approach using primary and secondary data through a questionnaire of 396 respondents. This research was conducted at Soekarno Hatta Airport Jakarta, Juanda Airport Surabaya and Sultan Hasanuddin Airport Makassar. The data were analyzed using the AMOS SEM program. On Lion Airlines, analyze the effect of service quality on customer satisfaction and analyze the influence of the Low-Cost Carrier concept on customer loyalty on Lion Airlines. The results of this study indicate that: (1) Low-Cost Carrier has a positive and insignificant effect on Lion Air airline customer satisfaction. (2) Service quality positively and significantly affects customer satisfaction with Lion Airlines. (3) Marketing technology positively and significantly affects customer satisfaction with Lion Airlines. (4) Low-Cost Carrier has a positive and significant effect on Lion Airlines airline loyalty (5) Service quality has a positive and insignificant effect on Lion Air airline customer loyalty (6) Marketing technology has a positive and significant effect on Lion Air airline customer loyalty (7) Customer satisfaction has a positive and significant effect on Lion Air customer loyalty, (8) Low-Cost Carrier has a positive and insignificant effect on customer loyalty through Lion Air airline customer satisfaction. (9) Service quality has a negative and insignificant effect on customer loyalty of Lion Air airline. (10) Marketing technology has a positive and significant impact on Lion Air's customer loyalty through customer satisfaction. This shows that the Low Cost Carrier has a positive and insignificant effect on lion air airline customer loyalty through customer satisfaction. The benefits of research are to determine the variables that affect customer satisfaction and loyalty so that they can contribute to companies to improve service quality by using optimal marketing technology and always pay attention to service quality on an ongoing basis.